CONDITIONS OF STUDENT'S ACTIVATION IN TECHNICAL EDUCATION - MASTALERZ, Elzbieta (Journal of Technology and Information Education, 2009)
Author describes basic issues concerning student's activation goals and purposes of technical education, and correct conduct of technical lessons in schools. Conditions for practical technical activation are formulated basing on literature and research.
Keywords: activation; student; teacher; technical education